writing and its sensitization process - Rojas, Dora Cecilia; García Arias , Marlyn; Antonillez Quijano, Rosalin (Rastros Rostros, 2023)
Writing is a complex process that involves grammatical theory, text linguistics, spelling, syntax and pragmatics that relate different systems of meaning construction. Writing is, in a way, to put out one's thoughts, to expose one's inner self; when writing, one is able to witness a staging of the writer's subjectivity, who becomes an actor and spectator of his own work. Hence the difficulty and importance of writing. "Not only for the fixation or evidence of the handwriting, or for the certainty of the document; but also because writing allows us to recognize, not to say confront, each idea or proposal, each initiative or intention, each project or utopia".
Keywords: Literature; sensitization